Report of the Work of the National Joint Committee for Spanish Relief, The British Committee for Refugees from Spain and The Basque Children's Committee (1939)
1939 038-0069-005 REPORT OF THE WORK OF THE NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF THE BRITISH COMMITTEE FOR REFUGEES FROM SPAIN AND THE BASQUE CHILDREN'S COMMITTEE 292/946/38/69(V)